Clinical and Electrodiagnostic Findings in Patients with Peripheral Neuropathy and Inflammatory Bowel Disease. Issue 9 (September 2015) - Gondim, Francisco de A. A.; de Oliveira, Gisele R.; Teles, Benedito C. V.; Aquino, Patrícia de S.; Brasil, Érico F.; Carvalho, Allyne M.; Souza, Marcellus H. L. P.; Braga, Lucia L. B. C.; Rola, Francisco H.
Abstract : Background: Several neurological diseases, especially different types of peripheral neuropathy (PN) are common in inflammatory bowel disease (IBD). Methods: We prospectively evaluated the presence of PN in 121 patients with IBD (51 with Crohn's disease [CD] and 70 with ulcerative colitis [UC]) and 50 controls (gastritis and dyspepsia) over 3.5 years. Results: A total of 15 patients (12.4%) with small-fiber neuropathy and IBD (7 CD and 8 UC) and 24 patients (19.8%) with large-fiber PN (12 CD and 12 UC) were diagnosed. Small-fiber neuropathy affected 6% and large-fiber PN affected 4% of the control patients. Patients with CD with PN were older, had more metabolic complications and more severe motor involvement than patients with UC with PN. Carpal tunnel syndrome was more common in patients with UC. Sural and median sensory nerves were the most commonly and severely affected sensory responses. Tibial, peroneal, median, and ulnar compound muscle action potential amplitudes were also significantly decreased in patients with CD and UC. In general, sensory and motor amplitudes were a more sensitive marker for PN in patients with IBD than conduction velocities. Conclusions: In summary, PN is common in patients with IBD. It may be primarily related to IBD, phenotypically modified by metabolic complications. Its phenotype is diverse (most commonly small to predominantly axonal sensory large-fiber), but usually more severe in CD. It also includes ataxic and demyelinating forms. Results from our 10-year follow-up will elucidate the PN clinical course and the real impact of the comorbidities and new therapies. Abstract : Article first published online 19 May 2015.